Carriage of Extended-spectrum Beta-lactamase–producing Enterobacteriaceae and the Risk of Surgical Site Infection After Colorectal Surgery: A Prospective Cohort Study. (10th September 2018) - Dubinsky-Pertzov, Biana; Temkin, Elizabeth; Harbarth, Stephan; Fankhauser-Rodriguez, Carolina; Carevic, Biljana; Radovanovic, Ivana; Ris, Frederic; Kariv, Yehuda; Buchs, Nicolas C; Schiffer, Eduardo; Cohen Percia, Shimrit; Nutman, Amir; et al.
Abstract: Background: Antibiotic prophylaxis that covers enteric pathogens is essential in preventing surgical site infections (SSIs) after colorectal surgery. Current prophylaxis regimens do not cover extended-spectrum beta-lactamase–producing Enterobacteriaceae (ESBL-PE). We aimed to determine whether the risk of SSI following colorectal surgery is higher in ESBL-PE carriers than in noncarriers. Methods: We conducted a prospective cohort study of patients who underwent elective colorectal surgery in 3 hospitals in Israel, Switzerland, and Serbia between 2012 and 2017. We included patients who were aged ≥18 years, were screened for ESBL-PE carriage before surgery, received routine prophylaxis with a cephalosporin plus metronidazole, and did not have an infection at the time of surgery. The exposed group was composed of ESBL-PE–positive patients. The unexposed group was a random sample of ESBL-PE–negative patients. We collected data on patient and surgery characteristics and SSI outcomes. We fit logistic mixed effects models with study site as a random effect. Results: A total of 3600 patients were screened for ESBL-PE; 13.8% were carriers SSIs occurred in 55/220 carriers (24.8%) and 49/440 noncarriers (11.1%, P < .001). In multivariable analysis, ESBL-PE carriage more than doubled the risk of SSI (odds ratio [OR], 2.36; 95% confidence interval [CI], 1.50–3.71). Carriers had higher risk of deep SSI (OR, 2.25; 95% CI, 1.27–3.99). SSI caused by ESBL-PE occurred in 7.2% of carriers and 1.6% of noncarriers (OR, 4.23; 95% CI, 1.70–10.56). Conclusions: ESBL-PE carriers who receive cephalosporin-based prophylaxis are at increased risk of SSI following colorectal surgery. Abstract : Standard antibiotic prophylaxis administered before colorectal surgery does not cover extended-spectrum beta-lactamase–producing Enterobacteriaceae (ESBL-PE). We found that ESBL-PE carriers have more than twice the risk of noncarriers of developing surgical site infection following colorectal surgery.